Detrital zircon U/Pb ages from the Nankai subduction zone (Japan) - Pauline Cornard; Harriet Dawson; Kevin T Pickering (PANGAEA, 2024)
U-Pb zircon age dating was applied on U-channel samples (30cc) that were collected from sandy deposits in cores from IODP Site C0024 (one sample; frontal Nankai accretionary Prism), ODP Site 1177 (two samples; Western Shikoku Basin) and IODP sites C0011 (three samples) and C0012 (one sample; Eastern Shikoku Basin). Detrital zircon U-Pb ages were measured using the London Thermochronology Research Group facilities at UCL based on a New Wave Nd: YAG 213 nm laser ablation system coupled plasma-mass spectrometry. Real time U-Pb were processed using GLITTER data reduction software. Repeated measurements of external zircon standard Plesovice (TIMS reference 337.13 +/-0.37 Myr ago) and NIST 612 silicate glass were used to correct for instrumental mass bias and depth-dependent inter-element fractionation of Pb, Th, and U. 206Pb/238U ages are used for those grain younger than 1 Ga, and for zircon grains older than 1,000 Ma we used the 207Pb/206Pb ages to determine the crystallization age. To better constrain the sediment provenance along the Nankai subduction zone, we integrated published U-Pb zircon age to our study. These include (1) potential sediment sources, e.g., Nagara, Yodo, Tenryu, Kiso and Fuji rivers from Clift et al. (2013) (https://doi.pangaea.de/10.1002/tect.20033), the Yangtze and Yellow rivers from Huang et al. (2020) (https://doi.pangaea.de/10.3390/min10050398), the Shimanto Complex from Shibata et al. (2008) (https://doi.org/10.1111/j.1440-1738.2008.00626.x) and the Sanbagawa Belt from Tsutsumi et al. (2009) (https://doi.org/10.2465/jmps.080416) and (2) published zircon ages from the frontal accretionary prism ((ODP sites 1176 and 1177 and IODP sites C0006E and C0007E; Clift et al., 2013) (https://doi.pangaea.de/10.1002/tect.20033).